Artificial intelligence in real-time control : proceedings of the IFAC Workshop, Clyne Castle, Swansea, UK, 21-23 September 1988 - Rodd, M. G.; Suski, Gregory J. (IFAC proceedings series., 1989)
Artificial Intelligence in Real-Time Control documents the proceedings of the IFAC Workshop held in Clyne Castle, Swansea, UK, 21-23 September 1988. It includes two keynote addresses that discussed architectural issues for expert systems in real-time control; the problem of representing knowledge and reasoning; and the problems encountered in obtaining such information. Other papers contained in these proceedings are representative of the major research bodies active throughout the world in the application of AI techniques in real-time control, although it was inevitable that a Europe-based conference would highlight the work of the European groups. While AI is clearly still in the process of establishing itself, it is undoubtedly a major new area of engineering endeavor. Practical experience is still relatively limited, and many of the results discussed at this event were obtained through simulation or, in a few cases, from reduced practical experience. The importance, though, lies in the fact that many countries are pouring extensive resources into the attempt to control difficult processes by using AI techniques. The wide cross section of interest was demonstrated by the fact that many diverse industries were represented at the workshop-ranging from power-systems control to telecommunications, and into the steel industry.